Methods in Teaching Industrial Mechatronic Systems - Fedak, Viliam; Bauer, Pavol (Communications - Scientific Letters of the University of Zilina, 2007)
Explanation in courses from the field of mechatronics is enough difficult due to the complexity and variety of phenomena to be explained. The introduction of computer based learning enables to make the learning easier and visualisation of variables offers a deeper insight in the system behaviour. Moreover, the introduction of e-learning into the teaching praxis makes learning in the courses more attractive for students and easier for the understanding of the presented subject. The paper describes the e-learning support of the study programmes in industrial mechatronic systems. Topics in e-learning modules are structured hierarchically starting from a system level in order to face the students with an increased complexity (top down approach). Introduced interactivity and animations allow the students to acquire a possibly deep insight into the complex and dynamic interactions of a number of parameters in the mechatronic systems.
Keywords: no keywords